Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1972
DOI: 10.1107/s0567739472001111
|View full text |Cite
|
Sign up to set email alerts
|

The relation between space group symmetry and the properties of direct solutions based on the Σ2formula. A method for using centrosymmetric Σ2solutions for solving non-centrosymmetric structures

Abstract: The refinement criteria (consistency criteria) of the ~2 and tangent formulae are discussed. From these criteria the properties of ~z solutions in various space groups are evaluated. Structure determinations can then be divided into five categories according to the properties of the most consistent ~2 solution. In three of these, trivial phases are obtained. For solving non-centrosymmetric structures in which the ~z formula produces centrosymmetric phases (such as structures in P21), a new method (~2P method) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1973
1973
1998
1998

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…For (23) and (24) refinement criteria can be found in the same way as for (21) and (22) (Schenk, 1972c). The criterion of (23) is:…”
Section: Non-centrosymmetric Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…For (23) and (24) refinement criteria can be found in the same way as for (21) and (22) (Schenk, 1972c). The criterion of (23) is:…”
Section: Non-centrosymmetric Structuresmentioning
confidence: 99%
“…The forms of (25) and (26) show that all trivialities resulting from space-group symmetry (Schenk, 1972c) also occur with the quartet relationships.…”
Section: Non-centrosymmetric Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, each quartet in NQEST involves the pair ~h+ ~k--~,+k and ~0~+ ~m+ ~h+k having [Eh+d small. On the contrary, NTREST exploits triplets estimated negative in spite of the Since (Schenk, 1972) Owing to the well known tendency of this crystal structure to lose the enantiomorph, no satisfactory solution may be expected among the 14 sets. Accordingly the program warns the user that the enantiomorph is probably lost (ENANT calculated from published phases is >35°).…”
Section: Di(g)= Ii(g)/io(g) and II Is The Modifiedmentioning
confidence: 99%
“…Some of these difficulties have been dealt with by Schenk (1972), who indicated that they can be ascribed to the influence of the space group symmetry and the properties of the Y2 relation.…”
Section: Introductionmentioning
confidence: 99%